2020
DOI: 10.1111/rda.13653
|View full text |Cite
|
Sign up to set email alerts
|

Behaviour and reproductive performance of Nigerian native chickens subjected to different mating ratios for a short term

Abstract: To date, there is no reported standard mating ratio for Nigerian native chickens despite their large population in the country. This study investigated the effect of mating ratio on behaviour, semen quality and level of stress. Sixty‐three (9 cocks and 54 hens) sexually matured birds were randomly assigned to three mating ratios (MR) of 1 cock to 3 hens (1C:3H), 1 cock to 6 hens (1C:6H) and 1 cock to 9 hens (1C:9H), and each MR was replicated three times. Each cock spent 2 weeks in a particular MR before it wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Results from the current study showed that eCORT had no significant influence on the mating behavior of the cocks. In Nigerian indigenous chickens, mating ratio (1C:3H, 1C:6H and 1C:9H) has no significant effect on their mating behaviors (Iyasere et al, 2020). In the current study, a mating ratio of 1C:6H was adopted to avoid the establishment of social dominance among males.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Results from the current study showed that eCORT had no significant influence on the mating behavior of the cocks. In Nigerian indigenous chickens, mating ratio (1C:3H, 1C:6H and 1C:9H) has no significant effect on their mating behaviors (Iyasere et al, 2020). In the current study, a mating ratio of 1C:6H was adopted to avoid the establishment of social dominance among males.…”
Section: Discussionmentioning
confidence: 84%
“…Birds were housed in deep litter floors pens covered with 5 cm wood shaving (2m×5m, giving a stocking density of 590 g/m 2 ). Other descriptions of the poultry house are the same as that reported by Iyasere et al (2020). Birds were fed layers mash concentrate feed (16.5% CP and 2725-2980 kcal/kg metabolizable energy) at the rate of 120 g/bird/day (recommended quantity for laying bird), to prevent excess fat accumulation in the hens which could affect laying.…”
Section: Animals and Housingmentioning
confidence: 99%
“…The mating ratio in the studied area was 1:3 (cock: hen). In Nigerian native chickens, the recommended ratio at village conditions was 1:9 (cock: hen) [21]. In the existing situations, the cocks might be higher than the hens.…”
Section: E Mating Systemsmentioning
confidence: 99%